2018
DOI: 10.1155/2018/8302645
|View full text |Cite
|
Sign up to set email alerts
|

Quality Investing and Pricing Strategies by Startups: Impacts of Demand Uncertainties and Capital Constraint

Abstract: Investing in product quality for future growths or conserving cash flow to avoid bankruptcy is an important trade-off faced by many capital-constrained startups. Focusing on the trade-off, this paper proposes a two-stage model where a startup firm must earn profit above the survival threshold by the end of every stage. Considering impacts of the uncertainty of demand responsiveness to quality (DRQ), market shocks, and survival threshold, a hedge with price setting and quality investing is established against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In that sense, it is important to consider the connection between pricing capability and the international performance. Additionally, a crucial factor for startups to define pricing in overseas markets is to evaluate the price of the competitors' products [134]. Recently, a survey of worldwide startup owners showed that one factor that slows down this success is pricing [130].…”
Section: Relationship Of Competitive Skills With the Business Perform...mentioning
confidence: 99%
See 1 more Smart Citation
“…In that sense, it is important to consider the connection between pricing capability and the international performance. Additionally, a crucial factor for startups to define pricing in overseas markets is to evaluate the price of the competitors' products [134]. Recently, a survey of worldwide startup owners showed that one factor that slows down this success is pricing [130].…”
Section: Relationship Of Competitive Skills With the Business Perform...mentioning
confidence: 99%
“…Figure 1 shows the research model to be tested. tors' products [134]. Recently, a survey of worldwide startup owners showed that one factor that slows down this success is pricing [130].…”
Section: Relationship Of Competitive Skills With the Business Perform...mentioning
confidence: 99%
“…The second area focuses on the impact of DUR on the effectiveness of BCF and TCF [24][25][26]. Jing et al [27] demonstrated the impact of demand uncertainty on the selection of BCF and TCF for a capital-constrained retailer through a set of numerical experiments.…”
Section: Literature Reviewmentioning
confidence: 99%